2016
DOI: 10.1088/0031-9155/61/8/3222
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a formula describing the saturation correction of plane-parallel ionization chambers in pulsed fields with arbitrary repetition rate

Abstract: Gas-filled ionization chambers are widely used radiation detectors in radiotherapy. A quantitative description and correction of the recombination effects exists for two cases, for continuous radiation exposure and for pulsed radiation fields with short single pulses. This work gives a derivation of a formula for pulsed beams with arbitrary pulse rate for which the prerequisites of the two existing descriptions are not fulfilled. Furthermore, an extension of the validity of the two known cases is investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Both chambers were crosscalibrated against a capped Markus IC (M-IC, model 34045, PTW; cap: plastic, 1 mm water equivalent thickness) and EBT3 films at sample position. Recombination inside the ICs can be treated with the formalism of continuous irradiation [11], since the pulse duration (>100 ms) is much longer than the IC collection time ($10 ms). For the M-IC (electrode distance of 1 mm, applied voltage of 300 V) used for absolute dosimetry the recombination correction is according to the chamber data sheet 0.5% at a dose rate of 200 Gy/s and is therefore less and negligible for the mean dose rate of max.…”
Section: Beam Setting and Experimental Setupmentioning
confidence: 99%
“…Both chambers were crosscalibrated against a capped Markus IC (M-IC, model 34045, PTW; cap: plastic, 1 mm water equivalent thickness) and EBT3 films at sample position. Recombination inside the ICs can be treated with the formalism of continuous irradiation [11], since the pulse duration (>100 ms) is much longer than the IC collection time ($10 ms). For the M-IC (electrode distance of 1 mm, applied voltage of 300 V) used for absolute dosimetry the recombination correction is according to the chamber data sheet 0.5% at a dose rate of 200 Gy/s and is therefore less and negligible for the mean dose rate of max.…”
Section: Beam Setting and Experimental Setupmentioning
confidence: 99%
“…The approach presented included improvements to the numerical solution first presented by Karsch. 16 Gotz et al 15 demonstrated that none of the Boags's models could provide good agreement with data experimentally determined with the Advanced Markus chamber for chamber voltages > 100 V in the range of ultra-high DPP values (up to 1 Gy/pulse). Their results agree to a more recent study conducted by Petersson et al, 17 who have also investigated the Advanced Markus ionization chamber from high to ultra-high DPP electron beam range (10 mGy/pulse -10 Gy/pulse).…”
Section: Introductionmentioning
confidence: 96%
“…Gotz et al 15 have proposed a numerical solution to account for the ion collection efficiency of plane‐parallel ion chambers due to volume recombination taking into account the space charge effect when irradiated with high DPP beams. The approach presented included improvements to the numerical solution first presented by Karsch 16 . Gotz et al 15 demonstrated that none of the Boags’s models could provide good agreement with data experimentally determined with the Advanced Markus chamber for chamber voltages > 100 V in the range of ultra‐high DPP values (up to 1 Gy/pulse).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there has recently been an increased interest in studying ion recombination effects in ionization chambers exposed to beams of protons or heavier ions. At the time of this work, several new publications devoted to ion recombination correction in ionization chambers have appeared in the literature …”
Section: Introductionmentioning
confidence: 99%
“…At the time of this work, several new publications devoted to ion recombination correction in ionization chambers have appeared in the literature. [21][22][23][24][25][26] In the case of an active scanning beam, the dose rate in single proton pencil beams may be much higher than that in clinical photon and electron beams, or that observed in typical continuous dose rate proton beams used in ocular radiotherapy (0.43 Gy/s). 19 Since a single beamlet can within a few milliseconds deposit a dose of 2 Gy over its Bragg peak region, the maximum local dose rate may exceed hundreds of Gy/s.…”
Section: Introductionmentioning
confidence: 99%